The Mistakes of Regional Tax records on SIPD and Their Impact on BAPENDA Subang Financial Reporting - Nuraeni, Shofiah (Society : Jurnal Pengabdian Masyarakat, 2026)
This community engagement program was carried out to address several challenges faced by BAPENDA of Subang,  Accurate and orderly regional tax management is an important factor in supporting the quality of regional financial reporting has implemented the Regional Government Information System (SIPD) as a means of financial recording and reporting, but in its implementation, various regional tax recording errors have been found that have the potential to hamper he preparation of financial reports. The method used is practice-based mentoring through fieldwork observation, data collection, and tax data processing. The activity was carried out for six months at the Subang Regency BAPENDA, involving officials from the Finance Subdivision. The results of the activity show that technical assistance can reduce errors in local tax recording, particularly those related to account codes, tax classification, and payment amounts. This activity also speeds up the financial validation and reporting process and improves the quality of local financial reports. In addition, this community service activity increases the understanding and awareness of officials regarding the importance of accuracy and accountability in local tax management. In addition, this community service activity increased the understanding and awareness of officials regarding the importance of accuracy and accountability in regional tax management. Overall, this activity made a positive contribution to supporting more transparent and accountable regional financial management at the Subang Regency BAPENDA.